Preparation and Characterization of Co Doped Copper Oxide (II) Thin Films by 45º Angle Chemical Spraying Pyrolysis - A. Hussain, Afnan; A. Hassan, Mustafa; I. Hassoon, Khaleel (Al-Nahrain Journal of Science, 2020)
In this work, Co doped copper oxide (II) thin films (COTF) were deposited by chemical spray pyrolysis method. Structural analyses have conﬁrmed monoclinic polycrystalline for COTF deposited at 400 ºC substrate temperature. Compared with pure COTF, Co-doped samples showed larger grain size with distortion in the structure. With the increase of doping concentration the structure changes to amorphous. Bandgap energy was 2.45 eV before doping and 2.6 eV at 3% doping and began to decrease with increasing doping concentration. Activation energy was found to be 0.24 eV and it decrease with increase of doping. The Co (6%) doped –COTF are deposited on silicon substrate to fabricate CuO-Si heteroـ junction.